Poly‐ and Perfluorinated Alkyl Substances in Air and Water from Dhaka, Bangladesh. (22nd December 2021) - Morales‐McDevitt, Maya E.; Dunn, Matthew; Habib, Ahsan; Vojta, Simon; Becanova, Jitka; Lohmann, Rainer
Abstract: Bangladesh hosts extensive textile manufacturing, for some of which per‐ and polyfluorinated alkyl substances (PFAS) have been used to impart water and dirt repellency, among other things. Textile waste emissions to the atmosphere and discharge into rivers and other bodies of water could present a significant concern for human and ecosystem health, but there is little information on PFAS in Bangladesh. To assess the presence of ionic PFAS and their precursors in air and water from Dhaka, Bangladesh, polyethylene sheets were deployed for 28 days as passive samplers for neutral PFAS in outdoor air and water, while ionic PFAS were measured from discrete water grabs. Fluorotelomer alcohols (FTOHs) were detected at almost all sites in air and water; the most frequently detected compound was 6:2 FTOH, ranging from below instrumental detection limits (<IDL) to 70 ng m −3 in air and from <IDL to −19 ng L −1 in water. Of the ionic PFAS, perfluorobutanoic acid (PFBA), perfluorohexanoic acid, perfluorooctanoic acid, perfluorohexane sulfonic acid, and perfluorooctane sulfonic acid dominated in frequency of detection and magnitude, with concentrations ranging from 1.8 to 19.0 ng L −1 in surface waters. The prevalence of 6:2 FTOH and PFBA across sites probably reflects their use in textile manufacturing and could indicate the industry's switch to shorter‐chain PFAS alternatives. Environ Toxicol Chem 2022;41:334–342. © 2021 SETAC Abstract : Concentration of PFAS in air and water from Dhaka Bangladesh during winter (January–March) of 2020. Water concentrations were obtained from discrete water grabs, while air concentrations were derived from polyethylene (PE) passive sampling. FTS = fluorotelomer sulfonate; PFCA = perfluorocarboxylic acid; PFSA = perfluorosulfonic acid.